Frequency of 677C -> T and 1298A -> C polymorphisms in the 5,10-methylenetetrahydrofolate reductase (MTHFR) gene in Turner syndrome individuals - Santos,Kelly (2006)
Turner syndrome (TS) is an interesting model for investigating the association between methylenetetrahydrofolate reductase (MTHFR) gene polymorphisms and non-disjunction because of the high frequency of chromosomal mosaicism among patients with this syndrome. We determined the frequencies of MTHFR 677C -> T and 1298A -> C polymorphic mutations in 49 patients with TS and 200 control individuals. The frequency of the 677C -> T allele was 0.39 for patients and 0.29 for controls while that of the 1298A -> C allele was 0.28 for patients and 0.25 for controls. Genotype frequencies were shown to be different in patients and controls (chi2 = 12.143; p = 0.033), and this was attributable to the higher frequency of the C677C -> T /677C -> T genotype among TS patients. In homozygotes, this mutation might have an effect on somatic chromosome disjunction by decreasing MTHFR activity.